2015
DOI: 10.15640/ijmpa.v3n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Live Music in Oncology Waiting Rooms: Two Mixed Methods Pilot Studies

Abstract: Although music is frequently utilized in medical waiting rooms in an attempt to potentially decrease anxiety and enhance the environment, the mechanisms of how and why music might impact waiting rooms are not yet understood. More specifically, it is unclear how live music might affect environmental factors, patients, caregivers, staff, and the performing musicians. The purpose of these mixed methods pilot studies was to investigate the perceptions of patients, musicians, and staff members who experienced live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The participants were questioned regarding their perception of the time they had been waiting, the cleanliness of the facility, and the overall care provided by the clinic, among other questions. In a follow-up study, Silverman (2015) suggested that live music rather than no music resulted in positive perceptions of the waiting rooms, distracting from potentially stressful appointments (though there are likely to be both practical and financial constraints associated with the use of live music). Similarly, Dijkstra (2009) reported that playing classical music in a waiting area of a dental clinic reduced anxiety and stress as compared to a no music condition.…”
Section: Music and The Perception Of Healthcare Servicesmentioning
confidence: 99%
“…The participants were questioned regarding their perception of the time they had been waiting, the cleanliness of the facility, and the overall care provided by the clinic, among other questions. In a follow-up study, Silverman (2015) suggested that live music rather than no music resulted in positive perceptions of the waiting rooms, distracting from potentially stressful appointments (though there are likely to be both practical and financial constraints associated with the use of live music). Similarly, Dijkstra (2009) reported that playing classical music in a waiting area of a dental clinic reduced anxiety and stress as compared to a no music condition.…”
Section: Music and The Perception Of Healthcare Servicesmentioning
confidence: 99%